2016
DOI: 10.18632/oncotarget.11970
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized macrophage migration inhibitory factor is a potential new tissue marker and drug target in cancer

Abstract: Macrophage migration inhibitory factor (MIF) is a pleiotropic cytokine, which was shown to be upregulated in cancers and to exhibit tumor promoting properties. Unlike other cytokines, MIF is ubiquitously present in the circulation and tissue of healthy subjects. We recently described a previously unrecognized, disease-related isoform of MIF, designated oxMIF, which is present in the circulation of patients with different inflammatory diseases. In this article, we report that oxMIF is also linked to different s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 45 publications
3
52
0
Order By: Relevance
“…Since MIF has been directly implicated in the regulation of endothelial differentiation [84], we believe that MIF as a tumor promoter proves again that monocytes-derived ECs can be a subpopulation of M2-TAMs, reaching the tumor to favor angiogenesis by also making part of the blood vessel structures. Interestingly, an oxidized isoform of MIF was identified as a prognostic biomarker and therapeutic target in inflammatory disease and cancer [85,86], showing again that the pro-oxidative tumor microenvironment is playing a role in angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Since MIF has been directly implicated in the regulation of endothelial differentiation [84], we believe that MIF as a tumor promoter proves again that monocytes-derived ECs can be a subpopulation of M2-TAMs, reaching the tumor to favor angiogenesis by also making part of the blood vessel structures. Interestingly, an oxidized isoform of MIF was identified as a prognostic biomarker and therapeutic target in inflammatory disease and cancer [85,86], showing again that the pro-oxidative tumor microenvironment is playing a role in angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that circulating MIF can occur in two forms: oxidized MIF (oxMIF) and reduced MIF (redMIF) [64,65]. Accordingly, RedMIF is the isoform that can be more abundantly expressed, and is also detectable in healthy subjects, whereas oxMIF represents the disease-related isoform which is predominant in the blood and on the surface of cells isolated from patients suffering from chronic inflammatory disorders and cancer [64,65].…”
Section: Oxidized and Reduced Isoforms Of Mifmentioning
confidence: 99%
“…Thiele et al (2015) previously described that MIF occurs in two immunologically distinct conformational isoforms, and identified oxMIF as the disease-related isoform predominantly expressed in patients with inflammatory diseases (Thiele et al, 2015) and in cancer patients (Schinagl et al, 2016). As BaxB01 specifically binds oxMIF (Thiele et al, 2015), we investigated the antibody's PK and minimally effective dose levels, and defined the exposures associated with optimal pharmacological activity.…”
Section: Discussionmentioning
confidence: 99%